2010
DOI: 10.1007/s11274-010-0315-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultrasound amplitude and duty cycle on fungal morphology and broth rheology of Aspergillus terreus

Abstract: Effects of ultrasound amplitude and duty cycle on cultures of Aspergillus terreus are reported in a 25 l slurry bubble column sonobioreactor. Fermentations were carried out batchwise. A 2 k -factorial design with added central points was used. Sonication at any cycle and amplitude level did not affect biomass growth rate and yield relative to nonsonicated control, but did affect growth morphology. Ultrasound disrupted fungal pellets and caused the biomass to grow mainly as dispersed hyphae. Production of lovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…and Wickerhamomyces anomalus and found that power was the most significant parameter. On the other hand, Sainz Herrán et al ( 2010 ) studied the effects of US on Aspergillus terreus and observed that US affected fungal morphology but not the growth rate at any power.…”
Section: Resultsmentioning
confidence: 99%
“…and Wickerhamomyces anomalus and found that power was the most significant parameter. On the other hand, Sainz Herrán et al ( 2010 ) studied the effects of US on Aspergillus terreus and observed that US affected fungal morphology but not the growth rate at any power.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, K L a increased with the gas flow rate, but no significant variation of K L a values with temperature was found in the range tested, which amply covers the operating conditions expected for the culture of microorganisms. In previous works, the temperature was controlled at 28 °C in all sonicated fermentations. , Therefore, it is ensured that the temperature changes caused by ultrasound application have no effect on the K L a measurement.…”
Section: Resultsmentioning
confidence: 99%
“…This consequence is mainly attributed to the metabolite secretion mode, which usually takes place with pellet morphology. At the same time, the ultrasound application cycle was proven to be the most influential parameter. , …”
Section: Introductionmentioning
confidence: 99%
“…In the past, extensive experimental investigations for the rheological characterisation of pellet‐based cultivations were carried out [15,42,43,103–112]. Although it is important to determine the viscous properties of a cultivation medium in order to estimate the power input of a process, it is not possible to conclude on the mechanical stress of an individual pellet or its influence on the pellet morphology without making major system assumptions [92,113].…”
Section: Experimental Investigations For the Micromechanical Charactementioning
confidence: 99%